Adverse effects in the indiscriminate use of medicines in the COVID-19 pandemic: a look at chloroquine, hydroxychloroquine and azithromycin - Costa, Jesus Eden Bezerra da (2022)
Objective: The present study sought to analyze the existing scientific evidence to date on the adverse effects of the indiscriminate use of chloroquine, hydroxychloroquine and azithromycin in the COVID-19 pandemic. Material and Method: This is an integrative literature review with LILACS, PUBMED/MEDELINE and SCIELO databases, between 2019 and 2022. 75 articles were identified, of which 10 were used in the preparation of the work. the drugs chloroquine, hydroxychloroquine and azithromycin in the treatment of COVID-19 is low, due to the rapid spread and installation of the pandemic worldwide. It is necessary to carry out pragmatic clinical trials with a greater number of patients to analyze the effectiveness of fighting the coronavirus and the safety of using these drugs.